Argumentasi Kasasi Penuntut Umum Berdasarkan Kesalahan Judex Factie Memutus Perkara Penganiayaan - Dimas Yoga Budi Purnomo (Sebelas Maret University, 2019)
The aims of this research are the arguments of the Prosecutor proposed the Cassation against judex factie erred in applying the law things of persecution for not considering the presence of witnesses and evidence of the existence of the letter in a Supreme Court verdict Number 244 K/PID/2015 has been in accordance with article 253 of the Criminal Procedure Code. Find out what being a consideration in granting the Supreme Court judge of Cassation Prosecutor has in accordance with article 256 jo article 193 of the Criminal Procedure Code. The research method used was the normative legal research. Legal materials in the form of source material primary law and secondary law materials. Engineering analysis method using a deductive syllogism patterned thought. Reason of appeal by the public prosecutor is because the law does not apply judex factie properly. Based on the facts in the trial that the defendant was clearly doing the crime of persecution, but the judge cut off the defendant not proven conclusively do the criminal act of persecution and to relieve the defendant of all charges of the public prosecutor. A matter before the judge should consider carefully in advance any facts in the trial included evidence, but in this case the judge does not consider the existence of witnesses and evidence in the form of a letter of visum et repertum. Erred in applying the law by judex factie resulted in the defendant’s assertion of the public prosecutor so obviously the Supreme Court in cassation has been granted in accordance with article 256 jo article 193 of the Criminal Procedure Code.Keywords: Argumentation Of Cassation Submissions, Judex Factie, Assault, Evidence.